Multiple marginalized identities and internalized HIV stigma among people living with HIV in South Florida: An intersectional approach - Megan A. Jones; Elliott R. Weinstein; Steven A. Safren (PLoS ONE, 2025)
Internalized HIV stigma is associated with several adverse mental and physical health outcomes among people living with HIV (PLWH). PLWH and other marginalized identities may experience worse internalized HIV stigma due to minority stress and structural oppression. This study conceptualized intersectionality via a multiplicative approach and examined the associations between intersectional marginalized-group identities and internalized HIV stigma among a sample of PLWH in South Florida (N = 1343) using hierarchical linear regression models. Interaction terms within these models were used to test the effects of having more than one marginalized identity over and above the main effects of each single marginalized identity. Overall, participants reported moderate levels of internalized HIV stigma (M = 2.47, SD = 1.93, range 1−6) with main effects for those identifying with age, race, ethnicity, and/or gender marginalization experiencing higher levels. The interaction between gender and ethnic marginalization (b = 0.82) and the interaction between age and ethnic marginalization (b = 0.32), predicted significantly higher levels of internalized HIV stigma over and above the main effects of these variables on their own. Additionally, the interaction between age and racial marginalization (b = −0.54) and the interaction between age and sexual orientation marginalization (b = −0.47) both significantly predicted less internalized HIV stigma over and above the main effects of these variables on their own. Findings highlight the importance of considering how intersectional marginalized identifies influence PLWH’s internalized stigma. Data offers insight into the subgroups of PLWH who could benefit from targeted interventions to reduce internalized HIV stigma and improve HIV care outcomes.